FUNCTIONAL OGJECTS OF TEACHING ENGLISH AS A SOCIAL ASPECT IN THE EDUCATIONAL PROCESS - Kushakov, Yusup (Журнал иностранных языков и лингвистики, 2023)
In this article, main aims of teaching English are considered as social factors in the educational process. According to the author not only psychological factor of learning foreign languages is being promoted to a leading position. The others also can become the key element in teaching and learning foreign languages. The author highlights the main points in this direction.